Communicative Game-Based Learning in EFL Grammar Class: Suggested Activities and Students’ Perception - Fithriani, Rahmah (JEELS (Journal of English Education and Linguistics Studies), 2018)
The role of grammar instruction is inevitably important for second and/or foreign language mastery. Unfortunately, in practice, many English teachers in foreign language contexts such as in Indonesia still teach grammar deductively; that is, learners are provided the grammar rules and examples, are told to memorize them, and then are asked to apply the rules to other examples. This particular method of teaching is believed to produce learners who cannot use the language communicatively although they have considerable knowledge of grammar rules. It has also been seen as contributing to learners’ passive participation and negative feelings towards grammar learning. The aims of this paper are to give an alternative solution to that problem by offering some ideas of game-based activities and to investigate students’ perception of the implementation of communicative game-based grammar learning. Using pre- and post-study questionnaire, the research study was conducted with 30 adult EFL learners taking an after-class English course. The findings indicated that these activities were effective in creating a non-threatening and more relaxing grammar classes, changing students’ negative perception of grammar learning and improving their perceived communicative skills.